Management of Human and Material Resources in Local Government through Effective Strategies and Organizational Utilization - Abalaka J.N; Ajiteru S.A.R; Sulaiman T.H (International Journal of Economics and Management Sciences, 2025)
The study examines Nigeria's resource allocation and usage as the gap in the country's pursuit of sustainable progress. The primary goal of the study is to investigate how Nigeria has struggled to achieve the Sustainable Development Goals (SDGs) due to inefficient use and distribution of financial, human, and material resources. Human and material resources are essential in every aspect of a company. An organization's ability to advance in all directions might be hindered by poorly managed human and material resources. Resources management offers a systematic assessment, requisitioning, and approval process for the evaluation and acquisition of products, equipment, and resources. The goal of resources management is to continuously seek opportunities to reduce costs and improve performance through the cost-effective selection and standardization of products, equipment, and related processes. A successful and efficient local government system will be preceded by well-managed human resources and material resources. while preserving or raising the standard of the services and care that are offered to the public. Subjectivism serves as the ontological orientation in this study, which employs a qualitative approach grounded in interpretivist philosophy. According to the study's findings, corruption, ethnic prejudices, poor governance, a lack of accountability, a lack of transparency, and unnecessary expenditure on pointless activities have all contributed to Nigeria's egregious inefficiency in resource allocation and use. According to the study's conclusion, Nigeria would be headed toward sustainable development if appropriate project planning, implementation, monitoring, and evaluation were done transparently and resources were used and distributed effectively. Therefore, the report suggests that Nigeria adopt economic and technical efficiencies in the distribution and use of its resources in order to achieve the aims of sustainable development.